2004
DOI: 10.1016/j.apergo.2004.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding statistical power in the context of applied research

Abstract: Estimates of statistical power are widely used in applied research for purposes such as sample size calculations. This paper reviews the benefits of power and sample size estimation and considers several problems with the use of power calculations in applied research that result from misunderstandings or misapplications of statistical power. These problems include the use of retrospective power calculations and standardized measures of effect size. Methods of increasing the power of proposed research that do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 20 publications
0
77
0
5
Order By: Relevance
“…Thus, 408 days of observation time per group (ie, 102 persons per group, with mean stay of 4 days) was required to detect a 50% reduction in this rate with 80% power and significance (P) less than .05. 19,20 …”
Section: Setting and Samplementioning
confidence: 99%
“…Thus, 408 days of observation time per group (ie, 102 persons per group, with mean stay of 4 days) was required to detect a 50% reduction in this rate with 80% power and significance (P) less than .05. 19,20 …”
Section: Setting and Samplementioning
confidence: 99%
“…Although statistical differences were found in the results of the experiment, we acknowledge that the study did not have strong statistical power and was particularly limited by the small sample size as well as other aspects of statistical power (Baguley, 2004). Rather than focus on statistical power, the study reported here used participants with domain expertise in a naturalistic setting (Farrington-Darby & Wilson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The lowess curves correspond to the 50th percentile (the median) and the 20th percentile. The 20th percentile was chosen because it corresponds to the conventional rule of thumb that power should be approximately 80% (Baguley, 2004).…”
Section: Evaluating the Function Mud When The Distribution Is Not A Mmentioning
confidence: 99%